1995
DOI: 10.1097/00005373-199505000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Changes and Gut Barrier Function in Sequential Hemorrhagic and Endotoxic Shock

Abstract: Multisystem organ failure (MSOF) is the major cause of late death following trauma. The gut is hypothesized to be the source of an ongoing systemic inflammatory response that drives MSOF. It has also been suggested that while a single physiologic insult might not reliably cause MSOF, the addition of a delayed second stress will. This is known as the "two-hit" theory. The purpose of this study was to investigate the two-hit theory by observing the hemodynamic and bacteriologic response to a second stress in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…Microvascular changes are one explanation of the 'twohit' theory of multiple organ failure [17][18][19][20]. Gelfand et al [21] support the concept that the hemorraghic shock accounts for the septic complication, since they did not find any significant bacterial translocation within 6 h of hemorrhagic shock in the pig.…”
Section: Discussionmentioning
confidence: 99%
“…Microvascular changes are one explanation of the 'twohit' theory of multiple organ failure [17][18][19][20]. Gelfand et al [21] support the concept that the hemorraghic shock accounts for the septic complication, since they did not find any significant bacterial translocation within 6 h of hemorrhagic shock in the pig.…”
Section: Discussionmentioning
confidence: 99%
“…However, physiologic responses to two-hit models have not been well characterized [11][12][13]. Using aortic rings, Price et al have recently demonstrated that prior H/R alters vascular responsiveness following bacteremia [15].…”
Section: Introductionmentioning
confidence: 99%
“…11 morbidity and mortality in critically ill patients. 1 2 It is believed that hypoperfusion of splanchnic organs, [3][4][5] During acute haemorrhage, the splanchnic circulation is greatly affected by local and systemic regulatory resulting from trauma, haemorrhage or disease, is an important contributor to the development of multiple organ mechanisms, which may cause immediate and sustained hypoperfusion of the gastrointestinal tract. 12 Although failure (MOF) and death.…”
mentioning
confidence: 99%